Effect of Intrinsic and Extrinsic Motivation on Employee Productivity: Case of Le Grande Hotel Pecatu - I Nyoman Gede Astina; Dewi Ambarwati (Institut Pariwisata dan Bisnis Internasional, 2015)
This study aimed to determine the effect of intrinsic and extrinsic motivation on employeeproductivity at Le Grande Hotel Pecatu. The independent variables studied were Intrinsic Motivation (X1) and Extrinsic Motivation (X2) with the dependent variable is the Work Productivity (Y). Data sampling used questionnaires to 120 respondents, while sampling used simple random sampling method. The tests used to test the research instrument are in the form of test validity and reliability testing. Hypothesis testing used the F test and t test. The results showed that multiple regression analysis based on the results obtained by the equation: Y = 2,112 + 0,340X1 + 0,418X2. Based on the results of the most dominant variable affecting the Work Productivity Extrinsic motivation is variable with a regression coefficient of 0.418. Hypothesis testing using the F test and t test showed that simultaneous or partially intrinsic and extrinsic motivation have significant effect on employee productivity at Hotel Le Grande.